Consequences of type-2 diabetes mellitus and malaria co-morbidity on sperm paraters in men: a case-control study in a district hospital in the Ashanti region of Ghana (2023)
Type-2 diabetes mellitus (T2DM) and malaria infection are highly prevalent in Africa particu- larly, in the Sub-Saharan Region. A greater number of people in the Ghanaian population who have T2DM are also reported to harbor malaria parasites. This study aimed to investi- gate the influence of T2DM & Malaria co-morbidity on sperm parameters among patients in the Ashanti Region of Ghana. This hospital-based cross-sectional analytic case-control study comprised 254 adult male study participants comprising 80 T2DM & Malaria co-mor- bidity, 80 T2DM only, and 94 normal controls. A blood sample (10mL) was drawn from each participant to measure FBG, HbA1c levels, Testosterone levels, Total cholesterol, and determination of Malaria parasite density. Seminal fluid was also collected from each partici- pant for semen analysis. Sperm kinetics of the T2DM & Malaria co-morbidity group particu- larly; total motility, rapid progressive motility, and slow progressive motility were negatively affected compared to both T2DM only (p<0.0001) and the Normal control (p<0.0001). Nor- mal sperm morphology was significantly affected in the co-morbidity group compared to T2DM only (p<0.0001). Sperm vitality was also statistically significantly reduced in the T2DM & Malaria co-morbidity than in T2DM only (t (4)=-8.62; p<0.001). There was a signifi- cant decline in testosterone levels in the T2DM & Malaria co-morbidity group than in the T2DM only (p<0.0001) and the control (p <0.0001). In conclusion, T2DM and malaria infec- tion have a stronger propensity to alter sperm morphology and lower sperm motility and vitality.